Pengaruh Pelatihan Tanggung Jawab Sosial Pada Mahasiswa Senior Resident Di Asrama X - Nurul Aisyah; Yogi Pambudi; Ratna Djuwita (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2020)
Social responsibility is one factor that causes a person or group of people to identify him/herself as a part of palce and community. Research shows that Research shows that being unaware of their social responsibility is the cause of people’s ignorance towards their social surrounding. The purpose of this study was to determine the effect of social responsibility training in increasing social responsibility of a group of Senior Resident students in the dormitory of university “X”. The study was differentiate in four stages: Base line (pre- test), social responsibility training, action plan and posttest. This study involved 13 Senior Residents and 106 first year dormitory residents. Quantitative (questionnaires) and qualitative data (interview) was used to measure the training effect.The results of this study indicate an increase in Social Responsibility and Place Attachment in participants, although it is not significant, but data shows an increase of social responsibility in three times measurement. The implication of this study is the importance of sustainability of training and action plan to obtain significant results.